2014
DOI: 10.1016/j.tpb.2013.09.003
|View full text |Cite
|
Sign up to set email alerts
|

On learning dynamics underlying the evolution of learning rules

Abstract: In order to understand the development of non-genetically encoded actions during an animal's lifespan, it is necessary to analyze the dynamics and evolution of learning rules producing behavior. Owing to the intrinsic stochastic and frequency-dependent nature of learning dynamics, these rules are often studied in evolutionary biology via agent-based computer simulations. In this paper, we show that stochastic approximation theory can help to qualitatively understand learning dynamics and formulate analytical m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
42
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(46 citation statements)
references
References 75 publications
(134 reference statements)
1
42
0
Order By: Relevance
“…This model incorporates a commonly used learning rule as the individual's cognitive decision mechanism (Arbilly & Laland, 2014;Beauchamp, 2000;Beauchamp et al, 1997;Dridi & Lehmann, 2014;Dubois, Morand-Ferron, & Giraldeau, 2010;Hamblin & Giraldeau, 2009;Katsnelson, Motro, Feldman, & Lotem, 2012;Kurvers, Hamblin, & Giraldeau, 2012). We then tackle the second limitation by adding complexity to the environment beyond what has been possible with game-theoretic PS models and the experimental studies they generated.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This model incorporates a commonly used learning rule as the individual's cognitive decision mechanism (Arbilly & Laland, 2014;Beauchamp, 2000;Beauchamp et al, 1997;Dridi & Lehmann, 2014;Dubois, Morand-Ferron, & Giraldeau, 2010;Hamblin & Giraldeau, 2009;Katsnelson, Motro, Feldman, & Lotem, 2012;Kurvers, Hamblin, & Giraldeau, 2012). We then tackle the second limitation by adding complexity to the environment beyond what has been possible with game-theoretic PS models and the experimental studies they generated.…”
mentioning
confidence: 99%
“…Notwithstanding these difficulties concerning the origins of learning in groups, we choose to assume that our agents used learning rules to decide on tactic use, an assumption that is supported by a number of empirical studies. Learning rules, for instance, have been used in psychology, ethology and behavioural ecology for many years to model animal behaviour individually or in groups (Arbilly & Laland, 2014;Bush & Mosteller, 1951;Dridi & Lehmann, 2014;Estes, 1950;Hamblin & Giraldeau, 2009;Harley, 1981;Herrnstein, 1961;Krebs, Kacelnik, & Taylor, 1978;McNamara & Houston, 1985;Stephens, 1989). Moreover, in a series of producerescrounger experiments with nutmeg mannikins, Lonchura punctulata, Morand-Ferron and found that the group-level proportion of the join tactic adjusts to different environmental conditions by learning the payoffs associated with each tactic.…”
mentioning
confidence: 99%
“…All we need to explain is the evolution of learning rules (like strength of reinforcement, weighing of past interactions, exploration of behavioural repertoire) that allow individuals to adjust their behaviour during their lifetime. Dridi & Lehmann [43,44] give wonderful examples of how exploratory trial-and-error reinforcement learning rules evolve that allow individuals to solve an iterated prisoner's dilemma.…”
Section: Helping With Maximal Levels Of Conflictmentioning
confidence: 99%
“…Lack of mobility allows 'individual recognition' based on location, as is the case for ants interacting with their many partner species or for pollinators interacting with flowering plants. Moreover, memory capacities are apparently sufficient for learning through operant conditioning, with the evolution of crucial learning rule parameters subject to natural selection [43,44]. Indeed, it has repeatedly been argued that solving an iterated prisoner's dilemma game might not be as rare as often assumed because scientists were looking for strategies proposed by theoreticians, like tit-fortat, while animals make decisions differently.…”
Section: Helping With Maximal Levels Of Conflictmentioning
confidence: 99%
See 1 more Smart Citation